‘Wij zijn geen folklore, wij zijn een religie!’: Candomblé en de strijd om als Afrikaanse religie erkend te worden - van de Port, Mattijs (Religie & Samenleving, 2009)
‘An increasing number of priests from candomblé – an Afro-Brazilian spirit possession cult – publicly demand that their creed is recognized as a full-fledged ‘religion’. In this article I discuss how this demand is part of a larger political project whereby candomblé priests seek to assert their voice in the public sphere of Salvador, Bahia, thus to counter the all out appropriation of candomblé myths, symbols and aesthetics by cultural entrepreneurs, tourist organizations and other outsiders. While candomblé has proven quite successful in these attempts, I show that the demand to be recognized as a ‘religion’ comes at a price: far from being a neutral term, ‘religion’ is a thoroughly Christian format. All creeds that make a public claim to be a ‘religion’ thus require to refashion themselves along this Christian model.